Pengaruh Disiplin Kerja, Pelatihan, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pt. Alfa Scorpi Medan - Siti Irawati Parinduri; Daud Arifin (International Journal of Economics and Management, 2026)
This study aims to analyze the influence of work discipline, training, and the work environment on employee performance at PT. Alfa Scorpi Medan. The research problem stems from low employee performance, as evidenced by unmet work targets, suboptimal task execution, and a gap between company standards and actual employee performance. Additionally, the results of the pre-survey indicate that work discipline has not been fully implemented, training has not been effective, and the work environment is not conducive. This study employs a quantitative approach using an associative method. The population consists of all 40 employees at PT. Alfa Scorpi Medan, with a saturated sampling technique. Data collection was conducted via questionnaires, observations, and interviews. Data analysis utilized multiple linear regression, including validity and reliability tests, as well as classical assumption tests. The results indicate that, individually, work discipline, training, and the work environment have a positive and significant effect on employee performance. Collectively, these three variables also have a positive and significant effect on employee performance. This suggests that improving work discipline, enhancing the effectiveness of training, and fostering a conducive work environment can optimally boost employee performance.